Acanthocereus paradoxus (Cactaceae), a new endemic species from Jalisco, Mexico - González-Zamora, Pedro; Carrillo-Reyes, Pablo; Sánchez, Daniel (Phytotaxa, 2020)
Acanthocereus paradoxus sp. nov., an endemic narrow cylindrical cactus from the state of Jalisco is described and illustrated. The species can be distinguished by its narrow cylindrical mature stems, stem epidermis dull green with some dark green margins, the presence of four central spines, and a greater number of ribs and spines in young stems. A morphological  comparison with the other cylindrical members of Acanthocereus and sympatric species of the genus is provided. Data about its habitat and the conservation status are also given.